Towards the development of soybean resistance to Dectes texanus LeConte (Coleoptera: Cerambycidae): evaluation of conventional soybean resistance in the soybean plant introduction 165673, transcriptomic analyses, and gene silencing by RNA interference - Aguirre Rojas, Lina Maria (Kansas State University, 2019)
Dectes texanus (Coleoptera:Cerambyciade) larvae devastate soybeans in the U. S. midwestern states by girdling and tunneling inside the stems. Reduction of natural sunflower and ragweed hosts may have promoted the use soybean as a host since the late 1950s. Development of soybean varieties resistant to D. texanus is of importance to manage this pest since harvesting as soon as possible is the only option available to farmers to reduce yield losses. The soybean plant introduction (PI) 165673 reduces the number of D. texanus larvae, but survivors are still found at 21 d post infestation that may damage and girdle the PI165673 stems at the end of the growing season. Soybean resistance to D. texanus can be enhanced with the delivery of double stranded RNA (dsRNA) in planta to suppress gene expression by RNA interference (RNAi). DsRNA expressed in planta can be designed specifically to target and silence D. texanus genes important for development. D. texanus genes uniquely or highly expressed when fed soybean compared to those fed their natural hosts or artificial diet can be exploited to impair the development of D. texanus with RNAi. Although, dsRNA-based silencing is successful in other cerambycids, its use with D. texanus is untested. The objectives of this dissertation are: 1) to evaluate stem girdling and tunneling by D. texanus in soybean PI165673 at the end of the 2014 growing season in Kansas; 2) to compare the transcriptomes of D. texanus larvae fed soybean, wild sunflower, giant ragweed or artificial diet; and 3) to silence the Laccase2 (Lac2) and Chitin synthase2 (CHS2) genes in D. texanus by feeding larvae artificial diet coated with Lac2 or CHS2-dsRNA. The stems of infested PI165673 had 20% less tunneling by D. texanus larvae compared to the susceptible control K07_1544 at the end of the growing season in 2014 in Kansas. However, this result may be overestimated since the PI16563 plants had not reached full maturity and development compared to K07_1544. Therefore, assessment of stem tunneling (%) and girdling damage should be conducted in Southern States where the PI165637 can finish their development. The PI165673 resistance negatively affected the development and survival of D. texanus first instar larvae, but surviving larvae developed until the last instar stage before the end of the growing season in Kansas. These larvae can potentially gridle the PI165673 plants. A D. texanus de novo transcriptome was assembled for differential gene expression analyses. Five and six unigenes were commonly up-regulated and down-regulated in K07_1544-fed larvae compared to those fed wild sunflower, giant ragweed, or artificial diet (FDR < 0.05, fold change cut off ≥ ± 1.5). Unigenes coding for a lipocalin, an ecdysteroid kinase, and a major facilitator transporter were among the commonly up-regulated unigenes in soybean-fed larvae. Unigenes coding for two insect cuticle proteins, a glycosyl hydrolase 45, a transglutaminase, and a chitin binding peritrophin-A domain were among the commonly down-regulated unigenes in soybean fed larvae compared to either native host or artificial diet. Additionally, 41 and 13 unigenes were also up-regulated and down-regulated in larvae fed susceptible K07_1544 plants compared to those fed wild sunflower or giant ragweed, respectively. Cytochrome P450s, carboxylesterases, major facilitator transporters and glycoside hydrolases were the most represented protein families among the up-regulated unigenes in soybean-fed larvae compared to either native host. Up-regulation of unigenes involved in biotransformation of plant allelochemicals, transport of small solutes and hydrophobic molecules, and digestion of plant cell walls by larvae fed soybean may be an important factor in the ability of D. texanus to use soybean as a host. The Lac2 relative transcript level was at least 6 times lower in dsLac2-fed larvae compared to dsGFP and dsCHS2-fed larvae. However, there were no significant differences in abnormal adult morphology between dsRNA treatments. Differences in CHS2 transcript levels and larval chitin content were not detected between dsRNA treatments. Lack of treatment differences is most likely related to a small sample size in the experiment. In conclusion, the PI165673 resistance needs to be accompanied by other sources of resistance to reduce and prevent damage caused by D. texanus surviving larvae. Genes within the up-regulated protein families in larvae fed soybean could be used as potential targets for RNAi. However, further gene silencing studies are needed before soybeans expressing D. texanus targeted-dsRNA can be available.
Keywords: Dectes texanus; Host plant resistance; De novo transcriptome; Differential expression analysis; Gene silencing; RNA interference RNAi